Assessment of psychology testing in the Philippines focus on industries and national education.[article]. - Ramos, Exaltacion C.
Two areas of psychological testing are surveyed, namely industrial testing and national-education testing, for testing-related issues. This paper calls attention to the relative absence of efforts in test construction a d test validation, despite the great activity in psychological testing. The need to upgrade the competence level and to define the responsibilities of psychologists involved in psychological testing in heavily underscored.